2016
DOI: 10.3802/jgo.2016.27.e40
|View full text |Cite
|
Sign up to set email alerts
|

Extrafascial hysterectomy after concurrent chemoradiotherapy in locally advanced cervical adenocarcinoma

Abstract: ObjectiveTo evaluate whether adjuvant simple hysterectomy after concurrent chemoradiotherapy (CCRT) improves progression-free survival (PFS) compared with current standard care in locally advanced cervical adenocarcinoma (LACAC).MethodsWe reviewed a cohort of 55 patients with LACAC (International Federation of Gynecology and Obstetrics [FIGO] stage IB2, IIA2, IIB, III without distant metastasis) diagnosed and treated with radical CCRT at Peking Union Medical College Hospital between January 2004 and October 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…In our study, we found surgery following CCRT provided a superiority in AC patients on 3-year OS (68.6% vs. 52.8%, p = 0.044), compared with non-surgery group. This was consistent with the findings of a previous study from our hospital based on a smaller patient population, that 3-year PFS and LPFS also had a trend to increase in surgery group [16]. However, clinical response after CCRT was not balanced in present study, which could influence the outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we found surgery following CCRT provided a superiority in AC patients on 3-year OS (68.6% vs. 52.8%, p = 0.044), compared with non-surgery group. This was consistent with the findings of a previous study from our hospital based on a smaller patient population, that 3-year PFS and LPFS also had a trend to increase in surgery group [16]. However, clinical response after CCRT was not balanced in present study, which could influence the outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Surgical complications related to procedures following radiotherapy may be higher than expected (15). In the studied cases, hysterectomy procedures after radiotherapy probably had a longer duration than expected (2 h and 30 min).…”
Section: Pelvic Recurrence Any Recurrence ---------------------------mentioning
confidence: 58%
“…The use of concurrent chemoradiotherapy in locally advanced cervical carcinomas has shown an improved response to treatment and could justify the lower number of surgical indications, as observed in this study with fewer cases operated since 2003 (15,16). Although this study did not resolve the effect of chemoradiation on the therapeutic outcome, this study may have directed the perception that any gain with hysterectomy following radiotherapy using older protocols may have been compensated due to the higher rate of chemoradiation that has been recently applied.…”
Section: Pelvic Recurrence Any Recurrence ---------------------------mentioning
confidence: 69%
See 1 more Smart Citation
“…However, no consensus over the benefit of such adjuvant surgery in LACC has been reached in the literature ( 8 ). Advocates of additional surgery argue that early hysterectomy leads to better disease control and avoidance of more extensive surgery, such as pelvic exenteration, in the event of a future recurrence ( 7 , 9 ). On the other hand, adjuvant hysterectomy is not morbidity-free and the rate of grade-3 adverse events may be as high as 26.5% ( 8 ).…”
Section: Introductionmentioning
confidence: 99%